Issues in the application of Murabahah sale in banking: financing consumer goods and trade - Sadique, Muhammad Abdurrahman (Global Academic Excellence, 2018)
A study of the procedural aspects of Murabahah would reveal that its proper implementation in a financing context is challenging. Murabahah as practised in banking is a trading instrument in its original layout that has been adapted for financing purposes. Due to the forced nature of the application of Murabahah in banking, financing on the basis of Murabahah involves numerous conditions, laxity in the observance of which may make the transaction invalid from an Islamic legal perspective. In order to overcome issues arising in Murabahah based financing, implementation of equity-based modes such as Musharakah should be attempted where possible, such as in the context of trade financing. Murabahah is commonly used to finance the purchase of assets in a variety of forms, including financing consumer items as well as in trade financing, through local purchase as well as import. The current paper analyses important aspects involved in the application of Murabahah in the above areas, scrutinising practical aspects that are required to be carefully observed for the validity of the procedure in shari‘ah.